Medical treatment of ectopic pregnancy: case report - Chatbi, Zaineb; Fekkoul, Soukaina; Rhazi, Inas; Tahiri, Hafsa; Saadi, Hanane; Mimouni, Ahmed (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Ectopic pregnancy occurs when the embryo implants outside the uterine cavity. It is a leading source of morbidity and mortality within pregnancy. Methotrexate, a folic acid antagonist, has been widely used to treat appropriately selected ectopic pregnancies. We report the case of a 20-year-old woman, married, G2P0, having as antecedent a right tubal ectopic pregnancy benefiting from a right salpingectomy two years ago, who presents actually a paucisymptomatic ectopic pregnancy. Medical treatment with methotrexate was chosen with monitoring of the patient's hemodynamic status and hCG level.